Dynamic Response of Composite Lining Tunnel with Buffer Layer: An Analytical and Experimental Investigation. (23rd November 2020) - Fan, Kaixiang; Shen, Yusheng; Wang, Shuaishuai; Gao, Bo; Zheng, Qing; Yan, Gaoming; Min, Peng
Abstract : Composite lining is often designed for the mountainous tunnels in high-intensity earthquake areas. The application of the buffer layer will bring more advantages, while the shock-absorbing mechanism is still unclear currently. In this paper, based on the Fourier-Bessel series expansion method, the dynamic stress concentration factor of composite lining tunnel with buffer layer subjected to plane SV waves in the half-space is obtained. Then, the influence of geometric and mechanical parameters of the buffer layer on composite lining was systematically analyzed. Finally, the correctness of the analytical solutions is verified by series shaking table tests and numerical simulations. Results suggest that the buffer layer can play the role of "redistributing" the seismic load, and it can effectively reduce the dynamic responses of secondary lining but amplify in primary support. There is an optimal interval of the stiffness and thickness for the buffer layer. When the stiffness ratio of the buffer layer to surrounding rock is 1/10 ∼ 1/50 or the ratio of buffer layer thickness to inner diameters of secondary lining is 1/40 ∼ 1/20, the shock-absorbing performance is remarkable. The general damage observations in tests show that the crown, arch springing, and invert of composite lining in case of no buffer layer are prone to cracking under a strong earthquake. The invert of the composite lining is more susceptible to be damaged after adopting the buffer layer. In general, the analytical results were consistent with experimental and numerical results. The above study results may provide theoretical support and experimental data for the seismic design of composite lining tunnels.